The Comparison of Psychological Barriers Between Individuals with a History of Anterior Knee Pain, Anterior Cruciate Ligament Reconstruction, and Healthy Individuals - Emma F Zuk; Sungwan Kim; Julie P Burland; Neal R Glaviano (International Journal of Sports Physical Therapy)
# Background